Discursive practices around the body of the female athlete: An analysis of sport psychology interactions in elite sport - Cosh, S.; Tully, P. J.; Crabb, S. (Psychology of Sport and Exercise, 2019)
Objective: To examine the discursive practices surrounding athletes` bodies with a particular focus on a) how food, the body and agency around eating and exercising practices are constructed, as well as b) how dominant discourses and narratives are deployed. Method: A case study design was used, examining interactions from three female athletes with a sport psychologist regarding their body composition. The psychology sessions took place within an elite sport setting. Recordings from three initial psychology sessions were recorded. Analysis drew on a synthesis of discursive psychology and conversation analysis. Results: Competing depictions of food and the body were drawn on by the athletes and the psychologist in order to either reproduce or resist taken for granted notions about a need to reduce body composition to improve performance. Discursive tensions were evident in talk around female athletes` bodies, with a performance narrative functioning to regulate athletes` bodies, at the same time that athletes oriented to a dominant notion of the thin female body. Food was also variously constructed in moral terms and as a neutral energy source. Throughout the sessions, individual agency for the body and for resolving the `problem` of body composition was reproduced, with broader discursive and institutional practices overlooked. Conclusion: This study provides an in insight into how talk around the body and eating practices takes place within one institutional context occurring within an elite sport setting. In particular, this study highlights how potentially problematic discourses and practices are privileged and reproduced or resisted. Shifting the focus to technique rather than body modification and nutrition may be beneficial for athletes` wellbeing. Further implications for practice are discussed.